Metafory zwierzęce w Błogosławieństwie Jakuba (Rdz 49, 1-28) - Wajda, Anna Maria (Collectanea Theologica, 2019)
The relatively numerous references to animals in the blessing of Jacob (Gen 49: 1-28) show that the biblical author had a broad knowledge of nature. According to the current classification of living organisms and method of research used by modern zoology, it is stated that these observations do not have the characteristics of scientific research. In spite of this, they are the evidence of the clear-sighted observation of animals, which is reflected not only in the knowledge of the appearance of individual species, but also of specific behaviours related to their way of life. It concerns not only domestic animals, like the ass (cf. Gen 49: 14), but also wild representatives of the fauna. References concerning the latter apply to the species perceived as highly dangerous to man and domestic animals, that is the lion (cf. Gen 49: 9), snake (cf. Gen 49: 17) or wolf (cf. Gen 49: 27). Amongst the animals mentioned in the blessing of Jacob one can also distinguish those which aroused admiration because of their appearance, such as the doe (cf. Gen 49: 21). At the same time, it is essential to emphasise the fact that the wealth of animal metaphors is just a tool used to translate “God’s address” into human language.